A Cyclometalated NHC Iridium Complex Bearing a Cationic (η5‐Cyclopentadienyl)(η6‐phenyl)iron Backbone. Issue 61 (5th October 2021) - Malchau, Christian; Milbert, Tom; Eger, Tobias R.; Fries, Daniela V.; Pape, Pascal J.; Oelkers, Benjamin; Sun, Yu; Becker, Sabine; Prosenc, Marc H.; Niedner‐Schatteburg, Gereon; Thiel, Werner R.
Abstract: Nucleophilic substitution of [(η 5 ‐cyclopentadienyl)(η 6 ‐chlorobenzene)iron(II)] hexafluorophosphate with sodium imidazolate resulted in the formation of [(η 5 ‐cyclopentadienyl)(η 6 ‐phenyl)iron(II)]imidazole hexafluorophosphate. The corresponding dicationic imidazolium salt, which was obtained by treating this imidazole precursor with methyl iodide, underwent cyclometallation with bis[dichlorido(η 5 ‐1, 2, 3, 4, 5‐pentamethylcyclopentadienyl]iridium(III) in the presence of triethyl amine. The resulting bimetallic iridium(III) complex is the first example of an NHC complex bearing a cationic and cyclometallated [(η 5 ‐cyclopentadienyl)(η 6 ‐phenyl)iron(II)] + substituent. As its iron(II) precursors, the bimetallic iridium(III) complex was fully characterized by means of spectroscopy, elemental analysis and single crystal X‐ray diffraction. In addition, it was investigated in a catalytic study, wherein it showed high activity in transfer hydrogenation compared to its neutral analogue having a simple phenyl instead of a cationic [(η 5 ‐cyclopentadienyl)(η 6 ‐phenyl)iron(II)] + unit at the NHC ligand. Abstract : Iron power : A cyclometalated Fe(II) and Ir(III) complex based on the cationic (η 5 ‐cyclopentadienyl)(η 6 ‐phenyl)iron(II)]imidazole skeleton is reported. Compared to its neutral analogue without the [CpFe] + fragment, it is surprisingly active in the transfer hydrogenation of ketones. Mechanistic investigation on the reaction paths performed by DFT calculations provided a better understanding of the reaction mechanism, possible intermediates and the active species.